Analysis between two optical biometric devices in patients with cataract - Rodrigues,Francisco Wellington (2018)
ABSTRACT Objective: To evaluate the correlation of optical biometry and target with variable ages, anterior chamber depth, axial length, R1/K1 and R2/K2 established by two optical biometry devices in patients with cataract. Methods: The study included the analysis of 348 medical records, from which 503 cataract eyes were selected, which underwent evaluation by the optical biometric devices IOL Master 700 and Lenstar LS 900 in the period of April to July 2017. Data collected were: age, anterior chamber depth, axial length, R1/K1 and R2/K2. Results: The average of the biometrics obtained using Lenstar was 21.02, varying 3.46, more or less, with an average target of -0.02, varying 0.45. In relation to the IOL Master it was 21.19, with a variation of 3.40 and average target of -0.01, a variation of 0.11. It can be observed that despite close values in relation to the mean, there was significance (p<0.001). Axial length (p<0.001) and R1/K1 (p<0.001) had an influence on the difference of the biometric values between the devices. Conclusion: A high degree of clinical and statistical correspondence was observed between the results obtained by the biometry devices in patients with cataract.